Stimulating and limiting factors for the growth of investment potential of Ukrainian insurance companies - Svitlana Cherkasova, Tetyana Kalaitan, Nadiia Rushchyshyn, Igor Yaremko, Nataliia Yaroshevych (LLC “Consulting Publishing Company “Business Perspectives”, 2020)
The fact that the accumulated investment potential (IP) of insurance companies (IC) does not have a significant impact on the processes of economic growth in Ukrainian practice actualizes the task of researching the practice of investing in the activities of domestic insurers. The purpose of the study is to find out, classify and highlight the main factors that influence the formation of the Ukrainian IC’ IP and give recommendations for overcoming a number of related difficulties. According to the results of investigation of the Ukrainian insurance industry development trends in 2011–2018, it was concluded that rates of their IP accumulation are insufficient. There is a decrease in the aggregate value of insurers’ investment assets and a reduction in the composition of investment attractive financial instruments. Low efficiency and simplification of investment strategies of IC are noted. The factors that exert a stimulating and inhibitory influence on the investment processes in the Ukrainian insurance market were identified. Ways and tools were proposed to strengthen the effect of incentive factors and eliminate or minimize the effect of the considered restrictive factors that can be used in the practice of state regulation of the insurance industry of the country. Considering the examined factors should allow the state regulators making more effective decisions to improve the investment activity of insurers and enhance its importance in the development of the national economy.
Стимулюючі та обмежувальні фактори зростання інвестиційного потенціалу українських страхових компаній
Investment Management and Financial Innovations, 2020, 17(1), 85-96.
Keywords: investment assets; insurer’s activity; strategies; Ukraine; market development